Pengaruh Daya Tarik, Fasilitas, Harga, dan Aksesibilitas Terhadap Kepuasan Wisatawan dengan Analisis Linear Berganda: Studi Kasus : Danau Pading - Desti Syarani; Octavia Zulaikha; Mimi Lestari; Vindi Rachmadani; Nada Yuliana Rahma (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This research stems from the growing popularity of local tourism, including Pading Lake in Central Bangka Regency, a former tin mine developed into a tourist attraction. However, this destination still faces various management challenges, particularly in terms of attractiveness, facilities, pricing, and accessibility, which influence tourist satisfaction. The purpose of this study is to analyze the influence of attractiveness, facilities, pricing, and accessibility on tourist satisfaction, as measured by revisit intention. The study used a mixed-method approach, collecting data through questionnaires, interviews, observations, and documentation. The sample was determined using the Isaac and Michael formula, totaling 347 respondents from a population of 3,450 tourists. Data were analyzed using multiple linear regression using the Stepwise approach. The research findings indicate that revisit intention is influenced by five variables: tourism activities, road conditions, price competitiveness, location cleanliness, and parking availability. The tourism activity variable proved to be the most dominant with the highest coefficient value, while public facilities obtained the lowest average value and need to be improved. The final regression model was able to explain 54.5% of the variation in tourist satisfaction, indicating that other factors outside this study still have an influence. These findings demonstrate the importance of tourism managers prioritizing the development of tourism activities, increasing accessibility, and providing adequate supporting facilities to increase tourist satisfaction and loyalty.